Deep immunophenotypic dissection and clinical impact of T cells in the follicular lymphoma microenvironment - Sary El Daker; David Qualls; Andriy Derkach; Samida Beqaj; Leonardo Boiocchi; Venkatraman Seshan; Jeeyeon Baik; Menglei Zhu; Gilles Salles; Ahmet Dogan; Mikhail Roshal; Pallavi Galera (Haematologica)
Follicular lymphoma (FL) is an indolent B cell lymphoma with a heterogenous disease course, and patients may not require immediate treatment upon diagnosis. Scrutiny of its microenvironment may provide key insights into lymphomagenesis and enhancement of therapeutic options.